Renal artery stenosis: are there patients who benefit from intervention? - Kihm, Melanie Christine; Heilmeier, Britta; Zeier, Martin; Kihm, Lars Philipp (Experimental and clinical endocrinology & diabetes, 2016)
Atherosclerotic renal artery stenosis (ARAS) is one of the most relevant long-term complications of atherosclerotic disease. It is associated both with hypertension and increased renal and cardiovascular risk and overall mortality. Diagnostic modalities include non-invasive duplex ultrasound, dynamic magnetic resonance angiography (MRA) and computer tomography angiography (CTA) and are confirmed by using invasive renal angiography. Percutaneous revascularization of renal artery stenosis has been studied in various clinical trials. With regard to hypertension, several case series could show a clinical response to revascularization. However, the majority of randomized clinical trials could not confirm the correlation between intervention and the improvement of hypertension, kidney function, cardiovascular events, and mortality. Based on this predication the crucial tool in the treatment of ARAS is an optimal medical therapy, including statins, antihypertensive agents and platelet inhibition. Today the core point is to select subgroups and appropriate indications for better outcomes and avoiding unnecessary procedures very carefully. Therefore in patients with typical manifestations of ARAS including resistant or malignant hypertension, progressive decline of renal function, flash pulmonary edema or angina, renal artery intervention remains a sensible therapeutic option - after hemodynamic testing prior to revascularization. In the future further trials targeting patients who fulfill rational selection criteria need to be undertaken to confirm the efficacy of revascularization.
Gesehen am 14.03.2019